Unraveling the Differences between Gram-Positive and Gram-Negative Probiotics in Modulating Protective Immunity to Enteric Infections - Kandasamy, Sukumar; Vlasova, Anastasia N.; Fischer, David D.; Chattha, Kuldeep S.; Shao, Lulu; Kumar, Anand; Langel, Stephanie N.; Rauf, Abdul; Huang, Huang-Chi; Rajashekara, Gireesh; Saif, Linda J. (Frontiers in Immunology, 2017)
The role of intestinal microbiota and probiotics in prevention and treatment of infectious diseases, including diarrheal diseases in children and animal models, is increasingly recognized. Intestinal commensals play a major role in development of the immune system in neonates and in shaping host immune responses to pathogens. Lactobacilli spp. and Escherichia coli Nissle 1917 are two probiotics that are commonly used in children to treat various medical conditions including human rotavirus diarrhea and inflammatory bowel disease. Although the health benefits of probiotics have been confirmed, the specific effects of these established Gram-positive (G+) and Gram-negative (G−) probiotics in modulating immunity against pathogens and disease are largely undefined. In this review, we discuss the differences between G+ and G− probiotics/commensals in modulating the dynamics of selected infectious diseases and host immunity. These probiotics modulate the pathogenesis of infectious diseases and protective immunity against pathogens in a species- and strain-specific manner. Collectively, it appears that the selected G− probiotic is more effective than the various tested G+ probiotics in enhancing protective immunity against rotavirus in the gnotobiotic piglet model.